Postconcussion Postural Sway Variability Changes in Youth: The Benefit of Structural Variability Analyses - Quatman-Yates, Catherine C. (Pediatr Phys Ther, 2015)
PURPOSE: The purpose of this study was to evaluate the utility of postural sway variability as a potential assessment to detect altered postural sway in youth with symptoms related to a concussion. METHODS: Forty participants (20 who were healthy and 20 who were injured) aged 10 to 16 years were assessed using the Balance Error Scoring System (BESS) and postural sway variability analyses applied to center-of-pressure data captured using a force plate. RESULTS: Significant differences were observed between the 2 groups for postural sway variability metrics but not for the BESS. Specifically, path length was shorter and Sample and Renyi Entropies were more regular for the participants who were injured compared with the participants who were healthy (P < .05). CONCLUSION: The results of this study indicate that postural sway variability may be a more valid measure than the BESS to detect postconcussion alterations in postural control in young athletes.